Gadolinium-based bimodal probes to enhance T1-Weighted magnetic resonance/optical imaging - Yang, Chang-Tong; Hattiholi, Aishwarya; Selvan, Subramanian Tamil; Yan, Sean Xuexian; Fang, Wei-Wei; Chandrasekharan, Prashant; Koteswaraiah, Podili; Herold, Christian J.; Gulyás, Balázs; Aw, Swee Eng; He, Tao; Ng, David Chee Eng; et al. (ACTA BIOMATERIALIA, 2020)
Gd3+-based contrast agents have been extensively used for signal enhancement of T1-weighted magnetic resonance imaging (MRI) due to the large magnetic moment and long electron spin relaxation time of the paramagnetic Gd3+ ion. The key requisites for the development of Gd3+-based contrast agents are their relaxivities and stabilities which can be achieved by chemical modifications. These modifications include coordinating Gd3+ with a chelator such as diethylenetriamine pentaacetic acid (DTPA) or 1,4,7,10-Tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA), encapsulating Gd3+ in nanoparticles, conjugation to biomacromolecules such as polymer micelles and liposomes, or non-covalent binding to plasma proteins. In order to have a coherent diagnostic and therapeutic approach and to understand diseases better, the combination of MRI and optical imaging (OI) techniques into one technique entity has been developed to overcome the conventional boundaries of either imaging modality used alone through bringing the excellent spatial resolution of MRI and high sensitivity of OI into full play. Novel MRI and OI bimodal probes have been extensively studied in this regard. This review is an attempt to shed some light on the bimodal imaging probes by summarizing all recent noteworthy publications involving Gd3+ containing MR-optical imaging probes. The several key elements such as novel synthetic strategy, high sensitivity, biocompatibility, and targeting of the probes are highlighted in the review. The present article aims at giving an overview of the existing bimodal MRI and OI imaging probes. The review structured as a series of examples of paramagnetic Gd3+ ions, either as ions in the crystalline structure of inorganic materials or chelates for contrast enhancement in MRI, while they are used as optical imaging probes in different modes. The comprehensive review focusing on the synthetic strategies, characterizations and properties of these bimodal imaging probes will be helpful in a way to prepare related work. [Display omitted]